2013
DOI: 10.5455/ijmsph.2013.250620133
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices (KAP) regarding carbonated drinks among students of medical college of western Maharashtra

Abstract: Background: The consumption of high sugar contained carbonated drinks is more prevalent among youngsters. The excess consumption of carbonated drink has been associated with many adverse health effects. Aims & Objective: (1) To study Knowledge, Attitude and Practices (KAP) regarding consumption of carbonated drinks among medical students. (2) To suggest suitable recommendation for the health promotion. Material and Methods: A cross sectional descriptive study was conducted to assess the knowledge, attitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 1 publication
6
15
1
Order By: Relevance
“…In the present study, it was found that more than two-thirds (78%) of medical students drink carbonated drinks this value is comparable to high consumption of carbonated drinks of high school students of united states which was about two-thirds (65%) (27), but it is considered to be higher than US children and youth from 6 to 17 years of age which was found to be increased from 37% to 56% (28). Furthermore, in the present study it was found that the students were highly aware about side effects of carbonated drinks (94%) which is comparable to other studies (6,18). Moreover, the students were more aware about individual side effects as obesity (78%), osteoporosis (84%) and teeth decay (72 %) This is in controversy to the other study which revealed that only 28.2% of the participants identied the obesity as a side effect, 11% for osteoporosis and only 9.1% for teeth decay (18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, it was found that more than two-thirds (78%) of medical students drink carbonated drinks this value is comparable to high consumption of carbonated drinks of high school students of united states which was about two-thirds (65%) (27), but it is considered to be higher than US children and youth from 6 to 17 years of age which was found to be increased from 37% to 56% (28). Furthermore, in the present study it was found that the students were highly aware about side effects of carbonated drinks (94%) which is comparable to other studies (6,18). Moreover, the students were more aware about individual side effects as obesity (78%), osteoporosis (84%) and teeth decay (72 %) This is in controversy to the other study which revealed that only 28.2% of the participants identied the obesity as a side effect, 11% for osteoporosis and only 9.1% for teeth decay (18).…”
Section: Discussionsupporting
confidence: 83%
“…Although carbonated drinks have lots of hazards, it was found that carbonated drinks are the third most consumed beverage (18), which indicates that they are very popular, especially among youngsters (19). Soft drinks consumption is associated with a number of personal factors including the taste (20) and parental inuences (21)and environmental factors such as the availability of soft drinks, especially in the home (22,23), portion size (including the small price differential for larger portions) ( 24,25)and the level of exposure for marketing (26).…”
mentioning
confidence: 99%
“…Similar observations were also found by Gupta et al [5] Studies have shown that the frequent consumption of soft drinks can lead to change in body mass index [6,7] and increase the frequency of obesity in children. [8] It was seen in the study done by Kharde et al [4] that 48% children had started having soft drinks at early age of <10 years, while in the present study it has been found that around 49% of the students had started consuming soft drinks between the age of 11 and 15 years, and among them the main influencing factor to start consuming was taste. Similar observations about taste as a main influencing factor among 52% students shown by Rai et al [1] In this study, it has been found that average amount of soft drinks about 200 ml consumed by around 42% students, same figure was also seen in Jogdand et al [9] They have also shown that around 86% students prefer fruit juice or homemade drinks over soft drinks, which was almost similar to the present study.…”
Section: Discussionmentioning
confidence: 42%
“…Time duration for filling of questionnaire was noted and unnecessary questions were excluded. Modification were done (Kharde et al, 2013).…”
Section: Data Collection Tools and Materials Pre-testing Of Questionnmentioning
confidence: 99%
“…Scientific studies have declared how a one or two soft drinks a day can increase one's risk for many health problems. Some of them are obesity, diabetes, tooth decay, osteoporosis, nutritional deficiencies, heart disease, and many neurological disorders (Kharde et al, 2013 andHamad, 2019). For the percentage that consumed soft drinks, most of the students (38 %) intake were soft drinks one time a week and a small percentage (12.3%) once a month as shown in Figure (7).…”
Section: Soft Drinks Patternmentioning
confidence: 99%